Evaluation of neonatal intensive care unit mortality - Isik, Sehribanu; Turkbay , Dursun; Kadioglu Simsek , Gulsum; Kanmaz Kutman , Hayriye Gozde; Canpolat , Fuat Emre (Annals of Medical Research, 2022)
Aim: To evaluate neonatal intensive care unit (NICU) deaths in one of the largest obstetrics centers in Turkey in order to determine the causes of death in this high-risk group.Materials and Methods: We retrospectively analyzed all NICU deaths occurring between 2013 and 2018. The study included infants born alive at 22 weeks of gestation or older.Results: Of 102374 babies born in our hospital, 14768 infants (14.4%) were admitted to the NICU and 957 (6.48%) of those infants died before discharge. The most common causes of death were extreme prematurity or extremely low birth weight (31.5%), lethal anomalies (13.1%), and sepsis (8.2%). At younger gestational ages, causes associated with extreme prematurity and complications of prematurity were most common, while the death rate due to perinatal asphyxia and genetic or structural anomalies increased at older gestational ages.Conclusion: The causes of NICU deaths are multifactorial and vary with gestational age. Efforts to reduce NICU mortality should include preventing or delaying preterm delivery and identifying the most appropriate treatment modalities that may reduce the risk of respiratory distress, intracranial hemorrhage, necrotizing enterocolitis, and sepsis. In more mature infants, the main goal should be to prevent and treat perinatal asphyxia and determine the most appropriate treatment modalities for non-lethal anomalies.
Keywords: Neonate; neonatal intensive care units; neonatal mortality; infant mortality